O não ético do capital a partir do projeto ético político-ecológico de libertação em Dussel - Rodrigues, Fernandes Antonio Brasileiro (2018)
This research investigates the philosophy of liberation in Dussel, its genesis and evolution, assuming the fundamental and decisive influence of philosopher Karl Marx to that thought, in particular, from the concept of exteriority. This is understood as being the area where the other reveals and manifests itself as a free being. Stem from the exteriority as the main category of thought in Marx, and fundamental theoretical assumption, Dussel's speech becomes feasible, in particular, as a thinker who opts for the victim, which was constituted as the distinctive feature in his philosophical thinking. The work aims to study the ethical concern with the liberation of the man from the unethical of capital, implicit in the social relations of production, which in Dussel, pervades the political-ecological field in which humanity is denied. Given this, it is assumed that in Dussel's thesis there is a natural vocation for the victim: his thinking is directed and built, deliberately, in favor of the victim. The effort of this work is to show that the victim is the common thread of all his thought while Liberation Philosophy, passing through Ethics, Politics and Ecology, by taking the political mediation to reach an Ecological Material of Liberation. To do this, as an approach strategy, the categories exteriority and liberation signal the philosophical analysis to the necessary inclination along with the topic investigated, through the reading of Dussel's major works, in dialogue with the philosophy of praxis of Marx. As an outcome of the hypothesis raised, it is intended to show how Dussel's option for the victim demands from the Philosophy of Liberation a critical pretension of thought, under four perspectives: historically situate Dussel, the History of Philosophy in America and the Philosophy of Liberation, in the sense of expressing the echo of the oppressed since its origin; through an Ethics of Liberation, as a critical pretension of modernity; of an Ethics of Liberation from a Marxist rereading of Dussel, guided by the category of living labor which indicates the exploitation and domination of the worker, the victim; and an Ecological one, demanding a Political Praxis of Liberation based on an Ecological Material Reflection. Therefore, the philosophical work is challenged and provoked by the real need to go to the victim's aid, a demand of the Latin American people on their way to liberation. As for the results, it is emphasized the understanding of reality and the critique of the capitalist system with emphasis on the philosophical theoretical-practical reflection of Enrique Dussel, in the ecological field, which crosses all the others, ethical, political, economic, etc .; for their contributions in the chaotic contemporary scenario, for the courage to point to the other society that is beyond this one, modern and capitalist that oppresses and massacres the worker.